‘It was all about independence’: loss, division and rejuvenation amongst the East Timorese in Melbourne - Askland, Hedda Haugen (The Australian journal of anthropology, 2014)
In this article I explore some of the changes that have occurred in the East-Timorese community in Melbourne following independence. The focus of the paper is on the process of identification and how there has been a move from a collective identity towards social identity. Through contemporary anthropological conceptualisations of (collective) identity and Pierre Bourdieu's concepts of habitus and social field, I explore how divergence in pre-independence activism has led to parallel experiences of lost community and renewed feelings of belonging, and how the community is gradually moving from a focus on the homeland towards an emphasis on the community in exile.